2017
DOI: 10.1007/s11085-017-9815-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Oxide Phases Formed upon Internal Oxidation of Advanced High-Strength Steels

Abstract: The effect of Cr on the oxidation of Fe-Mn-based steels during isothermal annealing at different dew points was investigated. The Fe-Mn-Cr-(Si) phase diagrams for oxidizing environments were computed to predict the oxide phases. Various Fe-Mn steels with different concentrations of Cr and Si were annealed at 950°C in a gas mixture of Ar or N 2 with 5 vol% H 2 and dew points ranging from -45 to 10°C. The identified oxide species after annealing match with those predicted based on the phase diagrams. (Mn,Fe)O is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our previous studies [25,26] already showed that the oxides formed at the steel surface during annealing at high temperatures in relatively low oxygen partial pressure environments can be well predicted by thermodynamic calculations, as was validated by X-ray diffractometry (XRD). Apparently, local equilibrium exists between the steel surface and the annealing gas at high temperatures.…”
Section: A Surface Oxidesmentioning
confidence: 64%
See 1 more Smart Citation
“…Our previous studies [25,26] already showed that the oxides formed at the steel surface during annealing at high temperatures in relatively low oxygen partial pressure environments can be well predicted by thermodynamic calculations, as was validated by X-ray diffractometry (XRD). Apparently, local equilibrium exists between the steel surface and the annealing gas at high temperatures.…”
Section: A Surface Oxidesmentioning
confidence: 64%
“…[21][22][23] The transition from internal to external oxidation of Fe-Mn alloyed steels have been studied [24] and it was observed that increasing the annealing dew point promotes internal oxidation. The oxides phases formed on Fe-Mn-Cr alloyed steels also have been studied with simulations and experiments [25,26] and showed that adding Cr to the Fe-Mn-based steel alloys results in the formation of (Mn,Cr,Fe) 3 O 4 spinel during annealing. Increasing the Mn concentration in the alloy promotes the formation of (Mn,Cr,Fe) 3 O 4 spinel and (Fe,Mn)O.…”
Section: Introductionmentioning
confidence: 99%
“…The EDS compositions after analyzing several different points on the Mn-Inc sample are summarized in SI Table S2, and the small amounts of Fe on the Mn-Inc surface varied significantly (1.5 ± 1.4 wt %). It is thermodynamically possible that the Fe species may have formed some mixed oxides of Mn and Fe (i.e., (Mn,Fe)O or Mn x Fe 3‑x O 4 spinel phases), but none of these were conclusively detected via XRD (Figure ), likely because the total Fe content was quite low. After the third coking cycle, the 2 theta positions of the MnO peaks slightly increased by 0.1–0.2°.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation occurs inevitably during the service of such micro/nano-sized alloy components, thereby affecting their surface properties [15][16][17][18][19]. Controlled pre-oxidation treatments of the fabricated alloys can be performed to tune and stabilize surface-related properties in an efficient and economical way [20,21]. The oxidation of crystalline ternary metallic alloys has been studied intensively in the past decades.…”
Section: Introductionmentioning
confidence: 99%